If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3.5x + 4 = 5 Reorder the terms: 4 + 3.5x = 5 Solving 4 + 3.5x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3.5x = 5 + -4 Combine like terms: 4 + -4 = 0 0 + 3.5x = 5 + -4 3.5x = 5 + -4 Combine like terms: 5 + -4 = 1 3.5x = 1 Divide each side by '3.5'. x = 0.2857142857 Simplifying x = 0.2857142857
| 3y^2+2xy=18-x^2 | | 3y^2+2xy=18-x^2fory | | x+.05x=999999 | | 5(4x+2)=37 | | 14x-3(5x-6)=27 | | 9x+4=4-(8x-9) | | 64+X=1728 | | 9x+4=4-(8x) | | h(x)=log(18x) | | 5a+10b=16.9 | | h(x)=18(x) | | 15(t)=22t-5t^2 | | h(t)=22t-5t^2 | | 15x+2x=7x+10 | | X^1/3-15x^1/3=-54 | | 4(b+1)+2(b+3)=10 | | 4(a-2)=3(a-1) | | 2*5-a=0 | | 3y+3+3y=7y+2-2y | | 2x^2-360x+15500=0 | | y=2x^3-10x^2-x | | 4-3x=6x+4 | | a^2+6a=4a-1 | | a^2+6a=4a-2 | | -3(z+5)=-2(z+1) | | 25x-19=6 | | 1-(5-2p)=3-(2p-5) | | 1-p=2-p | | X+7+5x-8=3+2x | | 8x+42=58 | | f(3a)=3a-9 | | -3(y-4)=5(y+3) |